Physico-chemical Studies of Water of River Yamuna at Mathura - Singh, Manvir; Gupta, K.C. (Asian Journal of Chemistry, 2010)
Physico-chemical characteristics of water of river Yamuna were studied from Jaisinghpura to Kachahari Ghat (a stretch of 6 km.) at Mathura. The duration of study was from April. 2002 to June 2002. Three sampling stations were selected for study The parameters under study were temperature, pH, turbidity, chloride, sulphate, total hardness, total alkalinity, total dissolved solids and metals like Cr, Fe, Cd, Pb, Ni, Mn, Zn and Cu. The concentrations of parameters like turbidity, chloride, sulphate, total hardness, TDS, Cr, Cd, Ni, Mn, Cu and Zn were found beyond the tolerance limits.